Ketiadaan Padanan Peribahasa Prancis dalam Bahasa Indonesia - Mardelana, Ismirani (Paradigma: Jurnal Kajian Budaya, 2016)
The absence of equivalents is an issue that has always been faced by translators in translating the source text. When translating proverbs, which are loaded with moral and cultural messages, translators are required to be able to transfer the messages appropriately. The different types of proverbs between French and Indonesian are a major cause of translators’ difficulty in finding the equivalents in the form of proverbs. This issue was raised from the author’s own experience in translating French fable by Jean de La Fontaine into Indonesian. By using the theory of Paremi and proverbs types of Bhuvaneswar (2000), French and Indonesian proverbs are analyzed in order to find the kinds of proverbs of the source language and the target language. It was found that the absence of equivalents in the form of Indonesian proverbs caused by the opposite of types of French proverbs and Indonesian proverbs. The majority of French proverbs are literal, whereas Indonesian proverbs are mostly metaphors. Data were taken from the fables of Jean de La Fontaine and its translation into Indonesian.